The effect of flow, thermodynamic and geometrical characteristics on exergy loss in shell and coiled tube heat exchangers. (November 2015) - Sadighi Dizaji, Hamed; Jafarmadar, Samad; Hashemian, Mehran
Abstract: This work presents experimental investigations on the effects of flow, thermodynamic and geometrical characteristics on exergy loss in shell and coiled tubes heat exchangers. Pressure drop and heat transfer characteristics in shell and coiled tube heat exchangers have been widely studied in the resent years. However, the effects of flow, thermodynamic and geometrical parameters on exergetic characteristics have not been explicitly and experimentally studied. Hence, the main scope of the present work is to clarify the effect of shell and coil side flow rates, inlet temperatures, coil pitch and coil diameter on exergy loss in shell and coiled tube heat exchangers. Both of the total exergy loss and dimensionless exergy loss are studied. Highlights: The effects of flow characteristics on exergy loss are investigated. The effects of thermodynamic characteristics on exergy loss are investigated. The effects of geometrical characteristics on exergy loss are investigated. Both of the exergy loss and dimensionless exergy loss are studied.